Effect of corrugation angle on the hydrodynamic behaviour of power-law fluids during a flow in plate heat exchangers - Fernandes, Carla S. (2011)
Hydrodynamic behaviour of a non-Newtonian fluid in PHEs channels with different corrugation angles was numerically studied and relations between Fanning friction factors and Reynolds number were developed, considering and discarding the effect of temperature on viscosity.